Gas Chromatography-Mass Spectrometry Profile of Essential Oils Derived from Zingiber officinale Rosc. Rhizome - Noval Dwi Wijaya; Lailatul Rohmah; Eria Anggraini; Rana Ayu Ning Tyas; Rizki Wahyu Aji Wibowo; Masruri MASRURI, Ph.D (The Journal of Pure and Applied Chemistry Research, 2020)
White ginger which is also called Jahe Putih (Zingiber officinale) in Indonesia, is widely used in local Indonesian communities. It is a popular ingredient in beverages for stamina and also a bioactive ingredient for many traditional Indonesian food recipes. It is a popular ingredient in beverages for stamina and also a bioactive ingredient for many traditional food recipes. However, with the increase in demand for ginger related products, fake ginger formulated products are widespread in the market. This paper is disclosed the chemical profile of essential oil obtained from steam distillation of the local ginger. The results of this study can be used as a standard to detect original ginger. It was found that the chemical composition of the essential oil obtained from the white ginger contained 0.19% of a dried weight after 3 h of steam distillation. A total of 40 monoterpenoids (C10) and sesquiterpenoids (C15) secondary metabolite compounds were respectively detected in the oil.